The Effect Of Massage Effleurage Therapy Towards Reduction Of Mental Pain In Adolescent Women At Sma Negeri 09 Medan In 2022 - Jitasari Tarigan Sibero; Indah Dewi Sari; Reni Asmita (Science Midwifery, 2022)
Massage effleurage is a movement using the entire surface of the hand attached to the abdomen which is rubbed lightly and soothingly. The massage of the abdominal effleurage massage stimulates the fibers in the skin to make it comfortable during uterine contractions so as to facilitate blood circulation to the uterus and block pain impulses to reduce. The purpose of this study was to determine the effect of massage effleurage therapy on the reduction of menstrual pain in adolescent girls at SMA Negeri 09 Medan in 2022. Methods: Using a pre-experimental research design with a one group pretest-posttest approach. The population in the study amounted to 52 female students who experienced mild menstrual pain and moderate menstrual pain in class XII SMA Negeri 09 Medan using purposive sampling obtained a sample of 10 people. Data analysis used univariate and bivariate analysis with Wilcoxon test. Results: From 10 respondents, before the effleurage massage was performed the highest category of moderate pain was 9 respondents (90.0%), the pain scale after the effleurage massage was the highest in the category of mild pain 8 respondents (80.0%). The average pain scale for effleurage massage got a mean of 2.1000 with a standard deviation of 0.31623. the pain scale after massage got a mean of 3.2000 with a standard deviation of 0.42164, indicating a decrease in pain scale in adolescent girls after effleurage massage. Conclusion: There is an effect of effleurage massage therapy on reducing menstrual pain in adolescent girls at SMA Negeri 09 Medan in 2022. It is recommended to respondents to increase their insight and knowledge about the benefits and how to do effleurage massage therapy, so that they can carry out effleurage massage therapy as a solution in handling pain during menstruation.